Pengembangan Media Monitoring Penyimpanan Arsip Dinamis Berbasis Dashboard pada Unit Sintelis PT KAI DAOP 8 Surabaya - Aurellia Kirana Bhanurasmi; Fatkhur Rochman (STIKes Ibnu Sina Ajibarang, 2026)
Dynamic records require effective management and monitoring to ensure the availability of information in a timely and accurate manner. The Sintelis Unit of PT KAI DAOP 8 Surabaya still monitors contract maintenance records using Google Spreadsheets and digital storage folders on computers. As a result, archival information is not integrated, making monitoring and retrieval activities less effective. This study aims to develop a monitoring media for contract maintenance records storage using a Looker Studio dashboard and to determine its effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The dashboard was developed using Looker Studio integrated with Google Spreadsheets as the data source and Google Drive as the digital records storage medium. The results show that the dashboard presents archival information in a visual, interactive, and integrated manner, facilitating records monitoring and retrieval. Evaluation using the Technology Acceptance Model (TAM) resulted in a Perceived Ease of Use score of 93.3%, a Perceived Usefulness score of 95.8%, and an Acceptance of IT score of 95.0%, all categorized as highly feasible. These findings indicate that the dashboard is easy to use, useful, and well accepted by users as a dynamic records monitoring media.